Purifications and characterizations of cholinesterase from different organs of Lates calcarifer Bloch - Mohd Hayat@Ahmad, Nursabrina (2015)
In Malaysia, many rivers such as Sungai Juru and Sungai Merbok have been greatly polluted by industrial effluents from electronics, basic and fabricated metal products, chemical plants, and transport equipment industries. Fish are ubiquitous organisms that have many features with a potential as a biomarker of heavy metals pollution. Recently, cholinesterase (ChE) from inhibition studies on fish has emerged to be one of the great potential biomarkers for heavy metals monitoring. The aim of this study was to assess the capability of ChE from selected Lates calcarifer organs namely brain, gill, liver, muscle, and kidney to detect metal ions because they tend to bioaccumulate and will give a great threat towards living organism. The ChE was purified through ammonium sulphate precipitation and ion exchange chromatography. The optimum ChE activity for all organs was determined to be at 25°C and in 0.1 M Tris-HCl buffer, pH 8.0. Each organ was able to hydrolyse different synthetic substrates. Brain, gill, and kidney showed a strong affinity towards acetylthiocholine iodide (ATC). Liver ChE hydrolysed butyrylthiocholine iodide (BTC) at a faster rate than other organs, while muscle ChE showed an optimum enzyme activity when propionylthiocholine iodide (PTC) was used as the substrate. Ten heavy metals namely argentum (Ag), arsenic (As),cadmium (Cd), chromium (Cr), copper (Cu), cobalt (Co), mercury (Hg), nickel (Ni), lead (Pb), and zinc (Zn) were chosen for the inhibition study. When tested with a specific substrate for each organ, the results showed that the brain ChE was inhibited by Ag, As, Cd, Cr, and Hg. Different results were obtained for gill ChE,which was inhibited by Cu, Hg, and Pb only, while liver ChE was inhibited by almost all of the heavy metals used, but only Cd and Co did not show an inhibition of >50%. Muscle ChE was inhibited by Pb, while kidney ChE was very sensitive towards Pb. The results showed that different substrates gave different inhibition effects towards the heavy metals. The results from this study can be further used in biomarker studies for addressing heavy metals pollution in water bodies.